POLENET/LAPNET teleseismic P wave travel time tomography model of the upper mantle beneath northern Fennoscandia - Silvennoinen, Hanna; Kozlovskaya, Elena; Kissling, Eduard (Solid Earth, 2018)
The POLENET/LAPNET (Polar Earth Observing Network) broadband seismic network was deployed in northern Fennoscandia (Finland, Sweden, Norway, and Russia) during the third International Polar Year 2007–2009. The array consisted of roughly 60 seismic stations. In our study, we estimate the 3-D architecture of the upper mantle beneath the northern Fennoscandian Shield using high-resolution teleseismic P wave tomography. The P wave tomography method can complement previous studies in the area by efficiently mapping lateral velocity variations in the mantle. For this purpose 111 clearly recorded teleseismic events were selected and the data from the stations hand-picked and analysed. Our study reveals a highly heterogeneous lithospheric mantle beneath the northern Fennoscandian Shield though without any large high P wave velocity area that may indicate the presence of thick depleted lithospheric “keel”. The most significant feature seen in the velocity model is a large elongated negative velocity anomaly (up to −3.5 %) in depth range 100–150 km in the central part of our study area that can be followed down to a depth of 200 km in some local areas. This low-velocity area separates three high-velocity regions corresponding to the cratonic units forming the area.